Pengembangan Lembar Kerja Siswa Berbasis Keanekaragaman Dan Kepadatan Populasi Tridacna Di Perairan Kepulauan Widi - Yulyanti Sudarmin; Rosita Tabaika; Lintal Muna (IAIN Ternate, 2022)
One of the rich fauna in the Widi Island, including coral reefs, seagrass beds, shellfish and fish. To preserve these fauna, especially shellfish, you can develop student worksheets that are used for the learning process on invertebrate material. The aims of the research were to develop LKS (Student Worksheets) based on the diversity and population density of Tridacna in the waters of the Widi Islands and to analyze the validity of student worksheets based on the diversity and population density of Tridacna in the waters of the Widi Islands. The development of LKS based on diversity and population density of Tridacna in the waters of the Widi Islands uses the ADDIE development model which consists of five stages. However, in this study the authors only reached the development stage, due to time and cost constraints. As for the development stage that the author did, namely the Analysis stage (Analyze), Design (Design) and Development stage (Develop). The validity level of LKS based on diversity and population density of Tridacna in the waters of the Widi Islands obtained an average score for the material expert validator, namely 3.87 with valid criteria. For media expert validators, an average score of 4.05 is obtained with valid criteria. The total average number of the two validators is 3.96 with valid criteria, so it can be concluded that student worksheets are feasible to use.Keywords: Development of LKS, Tridacna, Widi Islands